A History of the Isolation and Identification of Vitamin B6 - Rosenberg, Irwin H. (Annals of nutrition and metabolism, 2012)
In the 1930s, Rudolf Peters showed that young rats kept on a semi-synthetic diet with added thiamin and riboflavin but no other supplement developed ‘rat acrodynia’, a condition characterized by severe cutaneous lesions. In 1934, Paul György showed that the factor which cured ‘rat acrodynia’ was vitamin B 6 . Other studies soon showed that vitamin B 6 deficiency produced convulsions in rats, pigs, and dogs, and a microcytic anemia in certain animals. Samuel Lepkovsky isolated and crystallized vitamin B 6 in 1938. The following year, Leslie Harris and Karl Folkers, and Richard Kuhn and his associates independently showed that vitamin B 6 was a pyridine derivative, 3-hydroxy-4,5-dihydroxy-methyl-2-methyl-pyridine. György proposed the term pyridoxine for this derivative. Esmond Snell developed a microbiological growth assay in 1942 that led to the characterization of pyridoxamine, the animated product of pyridoxine, and pyridoxal, the formyl derivative of pyridoxine. Further studies showed that pyridoxal, pyridoxamine, and pyridoxine have largely equal activity in animals and owe their vitamin activity to the ability of the organism to convert them into the enzymatically active form pyridoxal-5-phosphate. Pyridoxal-5-phosphate plays a role in a wide variety of enzyme systems, especially in the metabolic utilization and transformation of amino acids.